Wyciek danych z systemu teleinformatycznego na przykładzie działalności wybranych organów administracji publicznej - Jałowiecka, Agata (Wydawnictwo C.H. Beck, 2023)
The subject of the study are issues related to the aspects of data leakage from the ICT systems of selected public administration bodies. The author brings up the subject of data leakage from the ICT system, the frequency of such incidents, the circumstances of electronic contact of an entity with local government branches and the bilateral transfer of data and documents, including via the ePUAP system. She also presents the consequences, ways of proceeding in the event of data leakage and good practices that should be followed to prevent such an event.
Keywords: wyciek danych; prawo administracyjne; prawo nowych technologii; system teleinformatyczny; administracja publiczna; ePUAP